Attenuation of thrombosis and bacterial infection using dual function nitric oxide releasing central venous catheters in a 9 day rabbit model. (15th October 2016) - Brisbois, Elizabeth J.; Major, Terry C.; Goudie, Marcus J.; Meyerhoff, Mark E.; Bartlett, Robert H.; Handa, Hitesh
Graphical abstract: Diazeniumdiolated dibutylhexanediamine (DBHD/N2 O2 ) based nitric oxide (NO) releasing catheters were fabricated and optimized using PLGA additive for sustained NO release for 14 d period. These nonhemolytic and noncytotoxic NO-releasing (NOrel) catheters were able to significantly reduce clotting and bacterial infection in a long-term rabbit model. Abstract: Two major problems with implanted catheters are clotting and infection. Nitric oxide (NO) is an endogenous vasodilator as well as natural inhibitor of platelet adhesion/activation and an antimicrobial agent, and NO-releasing polymers are expected to have similar properties. Here, NO-releasing central venous catheters (CVCs) are fabricated using Elast-eon™ E2As polymer with both diazeniumdiolated dibutylhexanediamine (DBHD/NONO) and poly(lactic-co-glycolic acid) (PLGA) additives, where the NO release can be modulated and optimized via the hydrolysis rate of the PLGA. It is observed that using a 10% w/w additive of a PLGA with ester end group provides the most controlled NO release from the CVCs over a 14 d period. The optimized DBHD/NONO-based catheters are non-hemolytic (hemolytic index of 0%) and noncytotoxic (grade 0). After 9 d of catheter implantation in the jugular veins of rabbits, the NO-releasing CVCs have a significantly reduced thrombus area (7 times smaller) and a 95% reduction in bacterial adhesion. These results show the promise of DBHD/NONO-based NO releasing materials as a solution to achieve extended NO release for longer term prevention of clotting and infection associated with intravascular catheters. Statement of Significance: Clotting and infection are significant complications associated with central venous catheters (CVCs). While nitric oxide (NO) releasing materials have been shown to reduce platelet activation and bacterial infection in vitro and in short-term animal models, longer-term success of NO-releasing materials to further study their clinical potential has not been extensively evaluated to date. In this study, we evaluate diazeniumdiolate based NO-releasing CVCs over a 9 d period in a rabbit model. The explanted NO-releasing CVCs were found to have significantly reduced thrombus area and bacterial adhesion. These NO-releasing coatings can improve the hemocompatibility and bactericidal activity of intravascular catheters, as well as other medical devices (e.g., urinary catheters, vascular grafts).